Semiotics and design: Towards an aesthetics of the artificial. (28th July 2017) - Holt, Matthew
Abstract: Semiotics is the theory par excellence of the artificial and therefore should have a substantial role in understanding designed phenomena. By tracing the relation between design and semiotics at the level of the distinction between the analytic and the synthetic (or artificial), this paper argues that semiotics struggles to explain the environmental element of design so central to post-artefactual accounts of design. The analytic method of semiology is suitable for understanding existent semiotic structures but less so at modeling alternate signifying systems—or systems that alter, transform and self-interpret, that is, environments. The paper argues that to understand such milieus a turn to the aesthetic is necessary. By aesthetics it is meant the simultaneous mapping of the environment, the articulation of the environment and the counterfactual element of any design process. More particularly the paper will focus on recent developments within social semiotics to argue that such a framework must move beyond the constraints of analytical spatial and visual grammar to take into account not only multimodal texts but planning, systems and services. It will conclude by arguing that ultimately design and aesthetics are the same phenomenon, not in the sense that design is the study and application of aesthetic principles to useful objects or experiences, but in the sense that it is the organization of the counterfactual elements of artificial—designed—environments.